Rate of Condition Causes Respiratory Failure - ali, Huda; abud, Suad; abud, Suad; hassan, Huda; abias, Simeia (Iraqi National Journal of Nursing Specialties, 2005)
Abstract : Objectives: The aims of the study are to identify the condition causes respiratory failure in both sex and to find out the relationship between prognosis and mortality rate with condition causes respiratory failure. Methodology : Descriptive study was carried out in Al- Yarmook Hospital in Respiratory care Unit in Baghdad from the 1st of August 2003 to 1st of August 2004, the sample consist of 300 patients (150) males and (150) females, descriptive and inferential statistics procedures were applied to the data analysis Results : The results shows that 24.4% of patients effect by post-operative complications and trauma as a results of respiratory failure , 11.3% from effected patients at age group (70-79)years and there are no significant relationship between prognosis and mortality rate with type of condition causes respiratory failure . Recommendation : The study recommends to preparing and training of recovery unit staff for respiratory resuscitation and patient care. Keyward : Respiratory Failure, Causes, Nursing.